EVALUATION OF SEDIMENT CONTROL STRUCTURE (SCS) PLACEMENT PLAN IN TUVA RIVER, SIGI DISTRICT - Khoir Marpaung, Alfin
The earthquake that occurred in 2018 caused landslides in the Sigi Regency. The Tuva River, a tributary of the Palu River administratively located in the Sigi Regency, experienced the aftermath of the landslide being carried downstream during heavy rainfall. The purpose of this research is to analyze the magnitude of flood discharge, as well as the patterns of aggradation and degradation of the Tuva River bed after various handling scenarios have been implemented, including the placement of structures, both hydraulically and in terms of erosion and sedimentation. Using the Hec-Ras 1D and 2D software with non-Newtonian features, the analysis revealed that the riverbed slope of the Tuva River falls into the steep classification with a slope ranging from 4 to 10%. Based on the 2019 data, the sedimentation volume in the Tuva River was found to be 15,416.99 m3/year. During periods of high rainfall intensity, there is a potential for ordinary sediment flood (Newtonian) with a discharge of 42,290 m3/second. When landslides are carried by the flow, there is a potential for debris flow (non-Newtonian) with a discharge of 54,971 m3/second and a sediment concentration of 30% in the flow. Consequently, the inundation area is expected to increase to 130-135% compared to the ordinary sediment flow (Newtonian). Following that, a 1-5 year flood probability analysis was conducted, revealing that the potential floods are likely to occur in the 2nd and 5th years with specific return periods. Subsequently, the daily discharge was combined with the planned flood discharge. The initial step in hydraulic modeling utilized the existing conditions, where the simulation results served as a guide for building placement using design scenarios: design scenario, alternative 1, alternative 2, alternative 3, alternative 4, and alternative 5. Based on the analysis, the placement using the design scenario and alternative 1 in the sedimentation zone can increase the water level, inundation area, downstream flow velocity of the Tuva River, and the static and dynamic slope of the consolidation dam. This can occur in a short period. For the placement of sediment control structures in the erosion zone (alternative scenarios 3 and 4), there is potential for riverbed scouring (degradation) downstream of the consolidation dam. Meanwhile, placing sediment control structures with alternative scenarios 2 and 3 can stabilize the riverbed and form more stable static and dynamic slopes.